Creatine monohydrate supplementation and muscular performance: effective, legal and safe
Cr supplementation is an effective, legal, and safe way to increase anaerobic muscular performance, especially in those sports or activities that require maximal or near-maximal repeated sprints. It appears that Cr supplementation increases the amount of Cr available for energy production, speeds recovery, and buffers lactic acid within the muscle cell. There are no known side effects of Cr supplementation aside from slight weight gain which has been attributed to water retention.